Root system architecture of paddy in phosphorus acquisition / Muhamad Khalis Azmi - Azmi, Muhamad Khalis (Faculty of Plantation and Agrotechnology, 2019)
The spatial arrangement of the plant root system architecture (RSA) is very sensitive to the availability of nutrient especially Phosphorus (P) which is an essential macronutrient and plays important roles in plant metabolism, growth and development. The objectives of this study are to observe RSA during P acquisition and to identify the length of seminal root (SR) together with the number of lateral root (LR) and crown root (CR). By using 0g, 0.01g and 0.1g of P in media as a treatment, the effects of nutrient acquisition toward RSA have been identified. After fourteen days of culture, images of RSA were taken by using DSLR cameras to make observation and root measurement was recorded to analyse the different effects between length and number of root to different amount of P. The result showed that the low P availability was found to favour LR growth over SR growth, by dramatically increasing LR elongation and inhibit SR growth. In CR formation, it was found that it is a special case of root formation which is highly dependent on auxin action. This shows that low P availability will increase the RSA while excessive P will inhibit it.